Qualidade de vida e saúde mental de estudantes universitários - Oliveira, Lycélia da Silva (2020)
It aims to quantify the level of Quality of Life and Mental Health of university students at a public higher education institution in Sobral, Ceará, Brazil. This is a quantitative, descriptive cross-sectional study. The population consisted of university students from the Vale do Acaraú State University. For the sample calculation, P was set at 50% and the significance level was 5% and the 95% confidence interval. The sample of participants consisted of 880 students. Inclusion criteria were students aged 18 years or over and attending university during the collection period, as well as acceptance in the Informed Consent Form. Data collection took place from April to June 2019 and was carried out in person and online. For data collection, a sociodemographic and academic questionnaire, the Whoqol Bref and the Mental Health Inventory were used. ANOVA, Chi-square test and Sperman's correlation coefficient were used. The research followed the ethical assumptions of the National Health Council and was approved by the Ethics Committee under Opinion No. 3,241,897. The study hypothesizes that UVA university students have low levels of Quality of Life associated with high levels of Mental Health problems. As a result, in the Physical Domain it presented an average of 60.6 ± 15.9, with the item on sleep having the lowest average with a value of 2.93. The Psychological Domain presented an average of 56.2 ± 18.6, in which the item corresponding to the students' concentration, presented a lower score, with a value of 3.05, followed by the frequency of negative feelings, with an average of 3.11. Social Relations had an average of 59.9 ± 20.8, with the greatest concern related to sexual life, with an average of 3.27. The Environment received the worst rating, with an average of 50.9 ± 14, with the item having money to meet needs, the lowest average with a value of 2.48. In general terms, in all domains a greater number of students with regular levels of Quality of Life is identified. In the Mental Health Inventory, the Ansiedade subscale exposed that the ability to relax showed a lower average, with a value of 36.29 ± 9.93. The Depression subscale has an average of 19.08 ± 5.33, with the symptom of greater concern being the symptom related to presenting in some measure the feeling of bad mood, with an average of 3.62. With regard to Loss of Emotional Control, an average of 34.77 ± 9.28 was found, with the item feeling emotionally stable with a lower average value, with a value of 3.40. In General Positive Affection, 37.21 ± 9.45 was found, with the item referring to questioning about life showing the greatest concern with an average of 2.73. In the Emotional Ties construct, mean values ​​and standard deviations of 11.01 ± 3.44 are found and thus show intense concern about the students' satisfactory love relationships, with this question being rated at 3.31. In general terms, 153 (17.38%) students are at low levels of Mental Health, while 571 (64.88%) are at moderate levels and 156 (17.72%) at high level. Thus, this research proves the initial hypothesis, indicating that most students have compromising levels of quality of life and mental health.